Childhood allergy susceptibility: the role of the immune system development in the in-utero period - Mohamad Zainal, Nurul Hayati; Mohd Nor, Nurul Huda; Saat, Azmah; Clifton, Vicki L. (Elsevier, 2022)
Expression of allergic diseases in very early childhood indicates that early life events play a significant role in childhood allergy development. The developmental origins of allergy hypothesis suggest events initiated in the in-utero period derived from the interaction between maternal, placental, and fetal factors may contribute to childhood allergy susceptibility. Environmental impacts on placental function and fetal programming are imperative in defining illness risk during pregnancy. Fetal programming, a process by which an injury delivered during a critical period of development, causes immediate adaptive responses with long-term consequences on an organism’s structure or function. During pregnancy, the maternal immune response is skewed towards Th2-related humoral responses, hence increasing the susceptibility of childhood allergy development. Maternal atopic phenotype markedly increases the probability of her offspring developing an allergic predisposition. Combination of in utero events – which include maternal asthma or infection, and exposures to maternal allergy which changes the placental function – can alter placental cytokine expression and could predispose offspring to an allergic phenotype. All these events may affect embryology and fetal immune system development. Interestingly, the mechanism and role of the in-utero events on the developmental origins of allergy are not clearly understood; this will be addressed in this review.